Potassium bismuth titanate-based ceramic with high energy storage density and excellent environmental stability and preparation method thereof
By introducing NaTaO3 and Bi0.5Na0.5TiO3 into bismuth potassium titanate ceramics, the problem of undustration of bismuth potassium titanate ceramics is solved, and ceramic materials with high effective energy storage density and environmental stability are achieved.
Patent Information
- Application Number
- CN202410681817.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-05-29
AI Technical Summary
Potassium bismuth titanate ceramics are not durable under high electric field strength and have low effective energy storage density.
By mixing Bi0.5K0.5TiO3 with NaTaO3 in a molar ratio of 0.85:0.15, and introducing Bi0.5Na0.5TiO3 modification, (1-x) (0.5Bi0.5K0.5TiO3-0.5Bi0.5Na0.5TiO3)-xNaTaO3 relaxed ferroelectric ceramics were synthesized by solid phase method.
At an electric field strength of 740 kV/cm, the effective energy storage density of the ceramic reaches 15.0 J/cm3, and it exhibits excellent stability under different environmental conditions.
Smart Images

Figure CN118619664B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of dielectric energy storage ceramic materials, and in particular relates to a potassium bismuth titanate-based ceramic with high energy storage density and excellent environmental stability and a preparation method thereof. Background Art
[0002] Dielectric ceramics are used as energy storage materials in devices such as defibrillators, cameras and mobile phones due to their high power density and fast charge and discharge speed. In order to make this material suitable for people's daily life, it needs to be non-toxic, miniaturized and integrated. At present, the main challenge faced by energy storage ceramics is to increase the breakdown field strength and reduce the polarization hysteresis to obtain a high effective energy storage density. Bismuth-based ceramics have become a research hotspot after lead-based ceramic capacitors due to the bismuth-oxygen coupling effect in their crystal structure.
[0003] Bismuth potassium titanate system ferroelectric ceramics have high spontaneous polarization intensity and have attracted attention in the field of energy storage materials. However, its high residual polarization intensity and low breakdown field strength limit its application. Studies have reported that by modifying it with other chemical components, it can be converted into relaxor ferroelectric ceramics, which can reduce the residual polarization intensity, polarization hysteresis and breakdown field strength while retaining its high polarization intensity, thereby improving the effective energy storage density and maintaining stable performance in changing environments, such as variable temperature, variable frequency or different number of cycles. Summary of the invention
[0004] The technical problem to be solved by the present invention is that potassium bismuth titanate ceramics are not resistant to high electric field strength and have low effective energy storage density, and therefore a relaxor ferroelectric ceramic with high effective energy storage density and environmental stability under high electric field strength is provided.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] First, 0.85Bi was prepared exploratory 0.5 K 0.5 TiO3-0.15NaTaO3 ceramics to confirm that the unmodified Bi 0.5 K 0.5 Can relaxor ferroelectric ceramics be obtained by mixing TiO3 and NaTaO3 in a molar ratio of 0.85:0.15?
[0007] In a second aspect, a bismuth potassium titanate-based ceramic having high energy storage density and excellent environmental stability is provided, wherein the chemical formula of the ceramic is: (1-x)(0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5TiO3)-xNaTaO3, wherein x is the doping coefficient of NaTaO3, x=0.0001-0.4, preferably x=0.06-0.24, and most preferably x = 0.18.
[0008] The ceramic is Bi 0.5 K 0.5 TiO3 is the matrix, 0.5 Na 0.5 After TiO3 modification, NaTaO3 was introduced and (1-x)(0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5 TiO3)-xNaTaO3 relaxor ferroelectric ceramics. In the embodiments, the value of x is 0, 0.06, 0.12, 0.15, 0.18, and 0.24.
[0009] When x is the optimal value of 0.18, the electric field strength that the ceramic can withstand reaches 740 kV / cm, and its effective energy storage density under this electric field is 15.0 J / cm 3 The main reason is that the Na in the introduced NaTaO3 component + and Ta 5+ Due to the difference in chemical valence and ion size between the A-site and B-site ions in the matrix crystal structure, the polarization between ions can be enhanced. At the same time, their introduction plays a role in increasing the disorder of ions, transforming the macroscopic ordered ferroelectric domains into disordered nano-domain clusters. Due to their small size, these domain clusters switch quickly under changing electric fields, effectively reducing the polarization hysteresis generated between the polarization processes of increasing and decreasing the electric field, thereby increasing the effective energy storage density.
[0010] The preparation method of the potassium bismuth titanate-based ceramic with high energy storage density and excellent environmental stability comprises the following steps:
[0011] S1: According to (1-x)(0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5 Weigh raw materials in a stoichiometric ratio of TiO3)-xNaTaO3, including a Bi-containing compound, a K-containing compound, a Ti-containing compound, a Na-containing compound and a Ta-containing compound, place the raw materials in a ball mill, add alcohol to perform ball milling, and then sequentially dry and grind to obtain a powder;
[0012] S2: pre-calcining the powder obtained in S1;
[0013] S3: adding a binder to the pre-fired powder in S2, grinding and granulating the powder, pressing the powder into tablets, and then placing the tablets in a muffle furnace for debinding and sintering in sequence to obtain the potassium bismuth titanate-based ceramic.
[0014] Preferably, in step S1, the Bi-containing compound is Bi2O3; the K-containing compound is one or both of K2CO3 and KHCO3; the Ti-containing compound is TiO2; the Na-containing compound is one or both of Na2CO3 and NaHCO3; and the Ta-containing compound is Ta2O5.
[0015] Preferably, in step S1, the ball milling time is 3-7 h and the rotation speed is 200-500 r / min, so as to fully mix the raw materials.
[0016] Preferably, in step S2, the pre-sintering temperature is 600-1000° C. and the time is 1-4 h, so as to obtain a precursor powder of synthetic ceramics.
[0017] Preferably, in step S3, the binder is a PVA aqueous solution with a mass concentration of 2-10%, the mass ratio of the binder to the powder is 0.02:1 to 0.1:1, the tableting pressure is 3-9 MPa, the debinding temperature is 300-800 °C, and the debinding time is 2-4 h; the sintering temperature is 1000-1300 °C, and the sintering time is 1-3 h.
[0018] The beneficial effects brought about by the technical solution provided by the present invention include at least:
[0019] The preparation method can obtain bismuth potassium titanate-based relaxor ferroelectric ceramics with high effective energy storage density and environmental stability, wherein 0.82 (0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5 The breakdown field strength of the TiO3)-0.18NaTaO3 relaxor ferroelectric ceramic is 740 kV / cm, which is higher than most bismuth-based energy storage ceramics. Its energy storage density is 15.0 J / cm 3 In addition, the ceramic also exhibits excellent environmental stability. Under the test conditions of 10-200Hz, the effective energy storage density is 10.90 ± 0.09 J / cm 3 ; in 10 1 -10 8 The effective energy storage density is 9.30 ± 0.13 J / cm 3 . BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 0.85Bi prepared in comparative example 0.5 K 0.5 Bipolar PE curve of TiO3-0.15NaTaO3 ceramics;
[0022] Figure 2 0.5Bi prepared in Example 1 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5 XRD patterns of TiO3 potassium bismuth titanate-based ferroelectric ceramics (x=0) and potassium bismuth titanate-based relaxor ferroelectric ceramics prepared in Examples 2-6 (x=0.06, 0.12, 0.15, 0.18 and 0.24);
[0023] Figure 3 is a SEM image of the potassium bismuth titanate-based relaxor ferroelectric ceramic (x=0.18) of Example 5;
[0024] Figure 4 1 is the unipolar PE curve of potassium bismuth titanate-based relaxor ferroelectric ceramic (x=0.18) of Example 5 under different electric field strengths;
[0025] Figure 5 The total energy storage density (W) of the potassium bismuth titanate-based relaxor ferroelectric ceramic (x=0.18) of Example 5 at different electric field strengths total ), effective energy storage density (W rec ) and energy storage efficiency (ƞ);
[0026] Figure 6 1 is a single-pole PE curve of the potassium bismuth titanate-based relaxor ferroelectric ceramic (x=0.18) of Example 5 at a test frequency of 10-200 Hz;
[0027] Figure 7 The potassium bismuth titanate-based relaxor ferroelectric ceramic (x=0.18) of Example 5 is heated to 10 1 -10 8 Unipolar PE curves under cycle number. DETAILED DESCRIPTION
[0028] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0029] Embodiment 1:
[0030] This example prepared 0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5 TiO3 ferroelectric ceramics include the following steps: 7.7659 grams of Bi2O3, 1.2092 grams of K2CO3, 0.8832 grams of Na2CO3 and 5.3244 grams of TiO2 are weighed according to the stoichiometric ratio, and the weighing error is between 0 and + 0.0005 grams. The weighed raw materials are poured into a ball mill, anhydrous ethanol is added and ball milled for 6 hours, and then the ball-milled sample is dried and ground. The mixed dry powder is placed in a crucible with a cover, and placed in a muffle furnace for pre-calcination at 820 ° C for 2 hours. After cooling, take an appropriate amount of powder, add 0.4 ml of a 5% PVA aqueous solution by mass fraction, grind and granulate, pour into a φ = 10 mm mold, press into a sheet using a cold isostatic press, and then place the sheet in a muffle furnace and sinter at 1120 ° C for 2 hours to obtain potassium bismuth titanate ferroelectric ceramics.
[0031] Embodiment 2:
[0032] This example prepared 0.94 (0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5 TiO3)-0.06NaTaO3 relaxor ferroelectric ceramics, including the following steps: 5.4750 grams of Bi2O3, 0.9916 grams of K2CO3, 0.7816 grams of Na2CO3, 4.3660 grams of TiO2 and 2.6513 grams of Ta2O5 are weighed according to the stoichiometric ratio, and the weighing error is between 0 and + 0.0005 grams. The weighed raw materials are poured into a ball mill, and anhydrous ethanol is added to the ball mill at a speed of 300 r / min for 6 hours. The ball-milled sample is then dried and ground. The mixed powder is placed in a crucible with a cover, and placed in a muffle furnace for pre-calcination at 820 °C for 2 hours. Take an appropriate amount of cooled powder and add 0.4 ml of 5% PVA aqueous solution to grind and granulate, pour into a φ = 10 mm mold and press into tablets using a cold isostatic press. Then, the tablets are placed in a muffle furnace and sintered at 1120 °C for 2 h to obtain potassium bismuth titanate-based relaxor ferroelectric ceramics.
[0033] Embodiment 3:
[0034] This example prepared 0.88 (0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5TiO3)-0.12NaTaO3 relaxor ferroelectric ceramics, including the following steps: weighing 6.8340 grams of Bi2O3, 1.0641 grams of K2CO3, 1.2012 grams of Na2CO3, 4.6854 grams of TiO2 and 1.7675 grams of Ta2O5 according to the stoichiometric ratio, with a weighing error between 0 and + 0.0005 grams. Pour the weighed raw materials into a ball mill, add anhydrous ethanol and ball mill at a speed of 300 r / min for 6 hours. Then dry and grind the ball-milled sample. Put the mixed powder in a crucible, cover it, and pre-sinter it in a muffle furnace at 820 °C for 2 hours. Take an appropriate amount of cooled powder and add 0.4 ml of 5% PVA aqueous solution to grind and granulate, pour into a φ = 10 mm mold and press into tablets using a cold isostatic press. Then, the tablets are placed in a muffle furnace and sintered at 1120 °C for 2 h to obtain potassium bismuth titanate-based relaxor ferroelectric ceramics.
[0035] Embodiment 4:
[0036] This example prepared 0.85 (0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5 TiO3)-0.15NaTaO3 relaxor ferroelectric ceramics, including the following steps: weighing 6.6010 grams of Bi2O3, 1.3601 grams of K2CO3, 0.9916 grams of Na2CO3, 4.3660 grams of TiO2 and 2.6513 grams of Ta2O5 according to the stoichiometric ratio, with a weighing error between 0 and + 0.0005 grams. Pour the weighed raw materials into a ball mill, add anhydrous ethanol and ball mill at a speed of 300 r / min for 6 hours. Then dry and grind the ball-milled sample. Put the mixed powder in a crucible, cover it, and pre-sinter it in a muffle furnace at 820 °C for 2 hours. Take an appropriate amount of cooled powder and add 0.4 ml of 5% PVA aqueous solution to grind and granulate, pour into a φ = 10 mm mold and press into tablets using a cold isostatic press. Then, the tablets are placed in a muffle furnace and sintered at 1120 °C for 2 h to obtain potassium bismuth titanate-based relaxor ferroelectric ceramics.
[0037] Embodiment 5:
[0038] This example prepared 0.82 (0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5TiO3)-0.18NaTaO3 relaxor ferroelectric ceramics, including the following steps: weighing 6.3681 grams of Bi2O3, 0.9916 grams of K2CO3, 1.3601 grams of Na2CO3, 4.3660 grams of TiO2 and 2.6513 grams of Ta2O5 according to the stoichiometric ratio, with a weighing error between 0 and + 0.0005 grams. Pour the weighed raw materials into a ball mill, add anhydrous ethanol and ball mill at a speed of 300 r / min for 6 hours. Then dry and grind the ball-milled sample. Put the mixed powder in a crucible, cover it, and pre-sinter it at 820 °C in a muffle furnace for 2 hours. Take an appropriate amount of cooled powder and add 0.4 ml of 5% PVA aqueous solution to grind and granulate, pour into a φ = 10 mm mold and press into a sheet using a cold isostatic press, then sinter the sheet in a muffle furnace at 1120 °C for 2 h to obtain potassium bismuth titanate-based relaxor ferroelectric ceramics. The ceramic sheet was polished to 50 μm, and gold was sprayed on the upper and lower surfaces to prepare electrodes for energy storage performance testing.
[0039] Embodiment 6:
[0040] This example prepared 0.76 (0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5 TiO3)-0.24NaTaO3 relaxor ferroelectric ceramics. Weigh 4.4266 g Bi2O3, 0.6892 g K2CO3, 1.1393 g Na2CO3, 3.0349 g TiO2 and 2.6513 g Ta2O5 according to the stoichiometric ratio, with a weighing error between 0 and + 0.0005 g. Pour the weighed raw materials into a ball mill, add anhydrous ethanol and mill at a speed of 300 r / min for 6 h. Then dry and grind the ball-milled sample. Put the evenly mixed powder in a crucible, cover it, and pre-sinter it at 820 °C in a muffle furnace for 2 h. Take an appropriate amount of cooled powder and add 0.4 ml of 5% PVA aqueous solution to grind and granulate, pour into a φ = 10 mm mold and press into tablets using a cold isostatic press. Then, the tablets are placed in a muffle furnace and sintered at 1120 °C for 2 h to obtain potassium bismuth titanate-based relaxor ferroelectric ceramics.
[0041] Comparative Example:
[0042] This comparative example prepared 0.85Bi 0.5 K 0.5TiO3-0.15NaTaO3 ceramics, including the following steps: 1.9803 grams of Bi2O3, 0.6167 grams of K2CO3, 0.3987 grams of Na2CO3, 1.3577 grams of TiO2 and 0.6628 grams of Ta2O5 are weighed according to the stoichiometric ratio, and the weighing error is between 0 and + 0.0005 grams. Due to the small total mass of the powder, the experiment uses a manual grinding method to mix the raw materials. Pour the weighed raw materials into a mortar, add anhydrous ethanol and grind with a grinding rod for 1 hour. Then dry the ball-milled sample. Put the evenly mixed powder in a crucible, cover it, and pre-sinter it in a muffle furnace at 820 °C for 2 hours. Take an appropriate amount of cooled powder and add 0.4 ml of 5% PVA aqueous solution to grind and granulate, pour into a φ = 10 mm mold and press into tablets using a cold isostatic press. Then, the tablets are placed in a muffle furnace and sintered at 1120 °C for 2 h to obtain potassium bismuth titanate-based ceramics.
[0043] Figure 1 0.85Bi prepared in comparative example 0.5 K 0.5 The bipolar PE curve of TiO3-0.15NaTaO3 ceramics is approximately square, indicating that this ratio cannot be used to prepare relaxor ferroelectric ceramics and cannot store energy normally. The main reason is that Bi 0.5 K 0.5 Bi and K in TiO3 are seriously volatilized, and the ceramic quality and performance are very poor. Therefore, the present invention designs to add Bi 0.5 Na 0.5 TiO3 chemical component can not only improve the quality of ceramics, but also enhance the polarization ability.
[0044] Figure 2 The powder X-ray diffraction patterns of the ferroelectric ceramic prepared in Example 1 and the relaxor ferroelectric ceramics prepared in Examples 2 to 6. Data analysis shows that Example 1 has a tetragonal perovskite phase, Examples 2 to 6 have a cubic perovskite phase, and all Examples are single phases.
[0045] Figure 3 : is a SEM image of the relaxor ferroelectric ceramic sample after sintering in Example 5. It can be seen that the ceramic grains are square with an average size of 0.3 μm. The submicron size is conducive to improving the breakdown field strength of the ceramic, thereby improving the effective energy storage density.
[0046] Figure 4 This is the unipolar hysteresis loop of the 50 μm thick relaxor ferroelectric ceramic sample prepared in Example 5 under a gradually increasing electric field at room temperature. It can be seen from the figure that the maximum electric field intensity finally reaches 740 kV / cm. It can be seen that their remnant polarization is small, the maximum polarization intensity is large, and the polarization hysteresis is small.
[0047] Figure 5 The energy storage performance parameters of the 50 μm thick relaxor ferroelectric ceramic sample prepared in Example 5 are shown in the figure at different test electric field intensities. It can be seen from the figure that the effective energy storage density reaches 15.0 J / cm at an electric field of 740 kV / cm. 3 .
[0048] Figure 6 This is the unipolar hysteresis loop of the 50 μm thick relaxor ferroelectric ceramic sample prepared in Example 5 at different test frequencies at room temperature. The test frequency is 10-200 Hz. Under this test condition, its effective energy storage density is 10.90 ± 0.09 J / cm 3 .
[0049] Figure 7 The unipolar hysteresis loops of the 50 μm thick relaxor ferroelectric ceramic sample prepared in Example 5 at different cycle times at room temperature, the cycle number is 10 1 -10 8 Under this test condition, the effective energy storage density is 9.3 ± 0.13 J / cm 3 .
[0050] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A potassium bismuth titanate-based ceramic with high energy storage density and excellent environmental stability, characterized in that: The chemical formula of the ceramic is: (1-x)(0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5 TiO3)-xNaTaO3, x=0.0001~0.
4.
2. The potassium bismuth titanate-based ceramic with high energy storage density and excellent environmental stability according to claim 1, characterized in that: x=0.06-0.24。 3. The method for preparing potassium bismuth titanate-based ceramics having high energy storage density and excellent environmental stability according to claim 1 or 2, characterized in that: The following steps are involved: S1: According to (1-x)(0.5Bi 0.5 K 0.5 TiO3-0.5Bi 0.5 Na 0.5 Weigh raw materials in a stoichiometric ratio of TiO3)-xNaTaO3, including a Bi-containing compound, a K-containing compound, a Ti-containing compound, a Na-containing compound and a Ta-containing compound, place the raw materials in a ball mill, add alcohol to perform ball milling, and then sequentially dry and grind to obtain a powder; S2: pre-calcining the powder obtained in S1; S3: adding a binder to the pre-fired powder in S2, grinding and granulating the powder, pressing the powder into tablets, and then placing the tablets in a muffle furnace for debinding and sintering in sequence to obtain the potassium bismuth titanate-based ceramic.
4. The method for preparing potassium bismuth titanate-based ceramics with high energy storage density and excellent environmental stability according to claim 3, characterized in that: In step S1, the Bi-containing compound is Bi2O3; the K-containing compound is one or both of K2CO3 and KHCO3; the Ti-containing compound is TiO2; the Na-containing compound is one or both of Na2CO3 and NaHCO3; and the Ta-containing compound is Ta2O5.
5. The method for preparing potassium bismuth titanate-based ceramics with high energy storage density and excellent environmental stability according to claim 3, characterized in that: In step S1, the ball milling time is 3-7 h, and the rotation speed is 200-500 r / min.
6. The method for preparing potassium bismuth titanate-based ceramics with high energy storage density and excellent environmental stability according to claim 3, characterized in that: In step S2, the pre-calcination temperature is 600-1000°C and the time is 1-4 h.
7. The method for preparing potassium bismuth titanate-based ceramics with high energy storage density and excellent environmental stability according to claim 3, characterized in that: In step S3, the binder is a PVA aqueous solution with a mass concentration of 2-10%, the mass ratio of the binder to the powder is 0.02:1 to 0.1:1, and the tableting pressure is 3-9 MPa.
8. The method for preparing potassium bismuth titanate-based ceramics with high energy storage density and excellent environmental stability according to claim 3, characterized in that: In step S3, the debinding temperature is 300-800 °C, and the debinding time is 2-4 h; the sintering temperature is 1000-1300 °C, and the sintering time is 1-3 h.